Lesson learnt: first reported case of complicated cutaneous pythiosis in a dog in Malaysia - Omar, Sharina; Lau, Seng Fong; Mohd Zainudin, N. A. I.; Azman, N.; Bay, Jessie Ji Xi (Veterinary Association Malaysia, 2019)
This report documents a case of 5-month old intact male German Shepherd dog diagnosed with pythiosis on its left forelimb. This is the first ever reported case of pythiosis presented at the University Veterinary Teaching Hospital (UVH), Universiti Putra Malaysia and may be the first ever reported incidence in Malaysia with a complaint of a chronic non-healing wound. The case became complicated as the dog was concurrently infected with a mixed bacterial infection and the identified bacteria were resistant towards a number of antibiotics tested. The antibiotic that was determined to be sensitive was only able to act on certain bacteria and not to the others. The journey of getting to the final diagnosis was almost impossible if we had not tried different media preparation: with and without Dermasel supplement; and through molecular approach using amplification at ITS region followed by DNA sequence analysis. The unwarranted lack during the diagnosis process of this incidence has made us more aware of the presence of Pythium insidiosum in Malaysia and plan for a more strategize ways of diagnosing the suspected fungus at laboratory setting in future. The objective of this paper is to share our experience and reflection on the diagnosis of the rare incidence of pythiosis present in Malaysia.